Energy‐Storage Electrodes: Room‐Temperature Metallic Fusion‐Induced Layer‐by‐Layer Assembly for Highly Flexible Electrode Applications (Adv. Funct. Mater. 30/2019). (23rd July 2019) - Song, Yongkwon; Kim, Donghee; Kang, Sungkun; Ko, Younji; Ko, Jongkuk; Huh, June; Ko, Yongmin; Lee, Seung Woo; Cho, Jinhan
Abstract : In article number1806584, Seung Woo Lee, Jinhan Cho, and co‐workers report a room‐temperature metallic fusion‐induced layer‐by‐layer assembly that can produce highly flexible paper electrodes with bulk‐metal like electrical conductivity. The introduced small‐molecule linkers minimize the separation distance between neighboring silver nanoparticles (Ag NPs), and consequently induce the metallic fusion of multilayered Ag NPs at room temperature without additional treatment.